Democratic reason : politics, collective intelligence, and the rule of the many - Landemore, Hélène, 1976- (Princeton University Press, 2013)
Individual decision making can often be wrong due to misinformation, impulses, or biases. Collective decision making, on the other hand, can be surprisingly accurate. In Democratic Reason, Hélène Landemore demonstrates that the very factors behind the superiority of collective decision making add up to a strong case for democracy. She shows that the processes and procedures of democratic decision making form a cognitive system that ensures that decisions taken by the many are more likely to be right than decisions taken by the few.
Keywords: Democracy.; Democracy -- Philosophy.; Majorities.; Majorité (Droit constitutionnel); POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Democracy; Democracy -- Philosophy; Majorities; Deliberative Demokratie; Demokratie; Entscheidungsfindung; Massendemokratie; Mehrheitsdemokratie; Politische Philosophie; Repräsentative Demokratie; Democratie.; Filosofische aspecten.